Seawater strontium isotopes, oceanic anoxic events, and seafloor hydrothermal activity in the Jurassic and Cretaceous - Jones, C; Jenkyns, H (2001)
There were three negative seawater strontium-isotope excursions (shifts to lower 87Sr/86Sr values) during the Jurassic and Cretaceous that were of relatively short duration (5-13 my) and showed a relatively quick recovery to pre-excursion 87Sr/86Sr ratios. These excursions occurred in the Pliensbachian-Toarcian (Early Jurassic), Aptian-Albian, and Cenomanian-Santonian (Early and Late Cretaceous respectively). Each excursion coincided closely in time with an Oceanic Anoxic Event (OAE) marked by sediments unusually rich in organic carbon. The Jurassic OAE occurred at the end of the strontium-isotope excursion, whereas the two Cretaceous OAEs occurred at the onset of the accompanying strontium-isotope excursions. The possible causes of these excursions were evaluated by successively examining the changes in the riverine strontium fluxes, riverine 87Sr/86Sr ratios, or hydrothermal strontium fluxes required to produce each excursion. A range of seawater strontium budgets was used to encompass the uncertainties in modern and ancient cycles. To produce the excursions, we calculate that the riverine strontium fluxes would have had to decrease by 6 to 15 percent or the fluvial 87Sr/86Sr ratios by 0.00019 to 0.00046. The uncertainties largely stem from the assumed magnitude of the hydrothermal strontium flux at the onset of each excursion. Alternatively, increases in sea-floor hydrothermal activity of 7 to 104 percent could also have produced the strontium-isotope excursions. This large range is due mostly to uncertainties in the relative flux of strontium from axial high-temperature hydrothermal systems and low-temperature off-axis systems. Only a small portion of this range stems from uncertainties in the riverine strontium terms. The possible causes of the excursions were further evaluated by examining several geologic factors that could have affected riverine strontium, including climate change, sealevel, and the eruption of flood basalts. We conclude that neither variations in riverine strontium fluxes nor in 87Sr/86Sr ratios is the likely cause of the strontium-isotope excursions. The most probable explanation is increased rates of hydrothermal activity related to increased ocean-crust production at the mid-ocean ridges. The close correlation in time between the strontium-isotope excursions and the major Oceanic Anoxic Events (OAEs) is compatible with a causal linkage. We propose that increased ocean-crust production led to enhanced CO2 outgassing and global warming, which in turn led to several processes that acted to make surface ocean waters more productive. However, because OAEs did not occur throughout the proposed periods of enhanced hydrothermal activity, it appears that these processes only preconditioned the oceans for the OAEs: sealevel rise may have been the final trigger. This model explains why all three OAEs did not occur at the same time relative to the onset of excess hydrothermal activity and why OAEs are not associated with every sealevel rise documented in the stratigraphic record.